Salmonella Phages Affect the Intestinal Barrier in Chicks by Altering the Composition of Early Intestinal Flora: Association With Time of Phage Use - Zhao, Hongze; Li, Yue; Lv, Peilin; Huang, Jinmei; Tai, Rong; Jin, Xiue; Wang, Jianhua; Wang, Xiliang (Frontiers in Microbiology, 2022)
Phages show promise in replacing antibiotics to treat or prevent bacterial diseases in the chicken breeding industry. Chicks are easily affected by their environment during early growth. Thus, this study investigated whether oral phages could affect the intestinal barrier function of chicks with a focus on the cecal microbiome. In a two-week trial, forty one-day-old hens were randomly divided into four groups: (1) NC, negative control; (2) Phage 1, 109 PFU phage/day (days 3–5); (3) Phage 2, 109 PFU phage/day (days 8–10); and (4) AMX, 1 mg/mL amoxicillin/day (days 8–10). The high-throughput sequencing results of cecal contents showed that oral administration of phages significantly affected microbial community structure and community composition, and increased the relative abundance of Enterococcus. The number of different species in the Phage 1 group was much higher than that in the Phage 2 group and differences in alpha and beta diversity also indicated that the magnitude of changes in the composition of the intestinal flora correlated with the time of phage use. Particularly in the first stage of cecal microbiota development, oral administration of bacteriophages targeting Salmonella may cause substantial changes in chicks, as evidenced by the results of the PICRUSt2 software function prediction, reminding us to be cautious about the time of phage use in chicks and to avoid high oral doses of phages during the first stage. Additionally, the Phage 2 samples not only showed a significant increase in the relative abundance of Bifidobacterium and Subdoligranulum, but also improved the intestinal morphology (jejunum), increased the mRNA expression level of occludin and ZO-1. We concluded that phages do not directly interact with eukaryotic cells. The enhancement of intestinal barrier function by phages in chicks may be related to changes in intestinal flora induced by phages. This implies that phages may affect intestinal health by killing pathogenic bacteria and regulating intestinal flora. This study provides new ideas for phage prevention of intestinal bacterial infections and promotes large-scale application of phages in the poultry industry.